Frequency, Determinants, and Outcomes of Emboli to Distal and New Territories Related to Mechanical Thrombectomy for Acute Ischemic Stroke. Issue 7 (20th May 2021) - Wong, Gregory J.; Yoo, Bryan; Liebeskind, David; Baharvahdat, Humain; Gornbein, Jeffrey; Jahan, Reza; Szeder, Viktor; Duckwiler, Gary; Tateshima, Satoshi; Colby, Geoffrey; Nour, May; Sharma, Latisha; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Clot fragmentation and distal embolization during endovascular thrombectomy for acute ischemic stroke may produce emboli downstream of the target occlusion or in previously uninvolved territories. Susceptibility-weighted magnetic resonance imaging can identify both emboli to distal territories (EDT) and new territories (ENT) as new susceptibility vessel signs (SVS). Diffusion-weighted imaging (DWI) can identify infarcts in new territories (INT). Methods: We studied consecutive acute ischemic stroke patients undergoing magnetic resonance imaging before and after thrombectomy. Frequency, predictors, and outcomes of EDT and ENT detected on gradient-recalled echo imaging (EDT-SVS and ENT-SVS) and INT detected on DWI (INT-DWI) were analyzed. Results: Among 50 thrombectomy-treated acute ischemic stroke patients meeting study criteria, mean age was 70 (±16) years, 44% were women, and presenting National Institutes of Health Stroke Scale score 15 (interquartile range, 8–19). Overall, 21 of 50 (42%) patients showed periprocedural embolic events, including 10 of 50 (20%) with new EDT-SVS, 10 of 50 (20%) with INT-DWI, and 1 of 50 (2%) with both. No patient showed ENT-SVS. On multivariate analysis, model-selected predictors of EDT-SVS were lower initial diastolic blood pressure (odds ratio, 1.09 [95% CI, 1.02–1.16]), alteplase pretreatment (odds ratio, 5.54 [95% CI, 0.94–32.49]), and atrial fibrillation (odds ratio, 7.38 [95% CI, 1.02–53.32]). Classification tree analysis identified pretreatment target occlusion SVS as an additional predictor. On univariate analysis, INT-DWI was less common with internal carotid artery (5%), intermediate with middle cerebral artery (25%), and highest with vertebrobasilar (57%) target occlusions ( P =0.02). EDT-SVS was not associated with imaging/functional outcomes, but INT-DWI was associated with reduced radiological hemorrhagic transformation (0% versus 54%; P <0.01). Conclusions: Among acute ischemic stroke patients treated with thrombectomy, imaging evidence of distal emboli, including EDT-SVS beyond the target occlusion and INT-DWI in novel territories, occur in about 2 in every 5 cases. Predictors of EDT-SVS are pretreatment intravenous fibrinolysis, potentially disrupting thrombus structural integrity; atrial fibrillation, possibly reflecting larger target thrombus burden; lower diastolic blood pressure, suggestive of impaired embolic washout; and pretreatment target occlusion SVS sign, indicating erythrocyte-rich, friable target thrombus.